Patients’ views about screening for atrial fibrillation (AF): a qualitative study in primary care - Miriam Santer; Michael Moore; Stephanie Hughes; Mark Lown; George Lewith; Christopher R Wilcox (BMJ Open)
Objectives There has been increased interest in screening for atrial fibrillation (AF) with commissioned pilot schemes, ongoing large clinical trials and the emergence of inexpensive consumer single-lead ECG devices that can be used to detect AF. This qualitative study aimed to explore patients’ views and understanding of AF and AF screening to determine acceptability and inform future recommendations.Setting A single primary care practice in Hampshire, UK.Participants 15 participants (11 female) were interviewed from primary care who had taken part in an AF screening trial. A semistructured interview guide was used flexibly to enable the interviewer to explore any relevant topics raised by the participants. Interviews were recorded, transcribed verbatim and analysed using inductive thematic analysis.Results Participants generally had an incomplete understanding of AF and conflated it with other heart problems or with raised blood pressure. With regards to potential drawbacks from screening, some participants considered anxiety and the cost of implementation, but none acknowledged potential harms associated with screening such as side effects of anticoagulation treatment or the risk of further investigations. The screening was generally well accepted, and participants were generally in favour of engaging with prolonged screening.Conclusions Our study highlights that there may be poor understanding (of both the nature of AF and potential negatives of screening) among patients who have been screened for AF. Further work is required to determine if resources including decision aids can address this important knowledge gap and improve clinical informed consent for AF screening.Trial registration number ISRCTN 17495003.